A Finite Mixture Von Mises Distribution for Wind Direction Analysis in Kuala Terengganu, Malaysia - Sanusi, Nortazi; Zaharim, Azami; Mat, Sohif; Sopian, Kamaruzzaman (International Journal of Engineering and Technology, 2018)
The complexity of its circular nature of data has limited research on wind direction compared to the linear form of wind speed. Nevertheless, the important role of wind direction is undisputable. This study is purposely to distinguish the best fit probability distribution for Kuala Terengganu’s wind direction data. Then, this probability distribution can be used in determining the best direction that able to capture the highest wind speed in that area. The numerical and graphical presentation of the wind direction will be discussed throughout this paper. Next, the coefficient determination, R2 is examined to ensure the appropriateness of this probability distribution. Finally, the analysis reveals that the wind direction data of Kuala Terengganu fits best with the four number of components (H=4) mixture model of von Mises.